The Role of Culture in Enhancing Students’ Language Acquisition: Teacher’s Strategy - Nasution, Ayau Ummad; Debataraja, Christina Suriani; Ningsih, Fitri Randia; Nasution, Ummi Aisyah; Daulay, Sholihatul Hamidah (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
The aim of this research is to understand the role of culture in enhancing students’ foreign language acquisition.  The researchers concluded that language and culture have a very close relationship. Therefore, this study wanted to examine whether the Ustadzah at the Darul Ihsan Islamic boarding school in the expanse of silver had implemented it in their classrooms properly. This research used a qualitative descriptive method. The research participants are two English teachers in Islamic boarding schools. The result of this study is that the teacher knows about the importance of understanding cultural literacy in a classroom then if a teacher wants to make students master the language well to speak and interact, a teacher should give an understanding to students about the role of culture in the use of cultural resources, literary culture and authentic ingredients.